Day-3-embryo fragmentation is associated with singleton birth weight following fresh single blastocyst transfer: A retrospective study - Cai, Jiali; Liu, Lanlan; Chen, Jinghua; Liu, Zhenfang; Jiang, Xiaoming; Chen, Haixiao; Ren, Jianzhi (Frontiers in Endocrinology, 2022)
Background Previous studies arguably associated poor embryo morphology with low birthweight in singletons following single embryo transfer. However, the association between specific morphological features in the cleavage stage and birthweight is still less known. The purpose of the study was to investigate whether embryo morphological features at the cleavage stage affect birthweight following blastocyst transfer Methods The single-center, retrospective cohort study included 4226 singletons derived from fresh single cleavage-stage embryo transfer (ET, n=1185), fresh single blastocyst transfer (BT, n=787), or frozen-thawed single blastocyst transfer (FBT, n=2254) between 2016 and 2019. The morphological parameters including early cleavage, day 3 fragmentation, symmetry, blastomere number, and blastocyst morphology were associated with neonatal birthweight and z-score in multivariate regression models. Models were adjusted for maternal age, BMI, parity, peak estradiol level, endometrial thickness, insemination protocol, female etiologies, order of transfer, mode of delivery, and year of treatment. Results Adjusted for confounders, fragmentation was the only morphology feature associated with birthweight and z-score, while early cleavage, symmetry, blastomere number, and blastocyst morphology were not. Fragmentation increased the birthweight in both ET group (115.4g, 95% CI: 26.6 to 204.2) and BT group (168.8g, 95%CI: 48.8 to 288.8), but not in the FBT group (7.47g, 95%CI: -46.4 to 61.3). The associations of birthweight and morphological parameters were confirmed in analyses for z-score. Adjusted odds of large for gestational age and high birthweight were also significantly greater in singletons following the transfer of fragmented embryos in the BT group (OR 3, 95% CI: 1.2 to 7.51, OR 3.65, 95% CI: 1.33 to 10, respectively). The presence of fragmentation at the cleavage stage also affected the association between blastocyst morphology and birthweight. Inner cell mass grades were negatively associated with birthweight in blastocysts with day 3 fragmentation but not in blastocysts without. Conclusions Birthweight following blastocyst transfer is positively associated with fragmentation at the cleavage stage. The data did not support the argument that transferring a poor-looking embryo may increase the risks of low birthweight. However, concerns for LGA infants still remain.